Antibacterial Activities of Caspir (Capsicum Frutescens L.) Leaves Gele Extrac Against Propionibacterium Acnes Causes of Acne - Anggraini Gobel; Srimuliani Arbie; Agusrianto Yusuf (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine the effectiveness of the spray gel preparation of cayenne pepper leaf extract (Capsicum frutesens L) in inhibiting the growth of Propionibacterium acnes bacteria and to determine the best concentration of the spray gel preparation of cayenne pepper leaf extract (Capsicum frutesens L) tested on acne-causing bacteria. The method in this study used a completely randomized design (CRD) with five treatments based on preparations with three concentrations, positive control and negative control. The treatments were: P1 (25% cayenne pepper leaf extract preparation), P2 (50% cayenne pepper leaf extract preparation), P3 (75% cayenne pepper leaf extract preparation), P4 (Control +), and P5 (Control -) . The results showed that the results of phytochemical screening for flavonoid compounds were positive and for the results of the inhibition zone testing of the extract preparations there was an average inhibition zone in the preparation with a concentration of 50% cayenne pepper leaf extract of 11 mm and 75% of 12 mm. While the results of statistical data analysis using One Way Anova get results > 0.05, which is 0.945, which means that H0 is accepted.